Polycyclic nitrogen heterocycles as potential thymidine phosphorylase inhibitors: synthesis, biological evaluation, and molecular docking study - Karen Aknin; Alexis Bontemps; Amaury Farce; Eric Merlet; Philippe Belmont; Philippe Helissey; Philippe Chavatte; Marie-Agnès Sari; Sylviane Giorgi-Renault; Stéphanie Desbène-Finck (Taylor & Francis Group, 2022)
New polycyclic heterocycles were synthesised and evaluated as potential inhibitors of thymidine phosphorylase (TP). Inspired by the pharmacophoric pyrimidinedione core of the natural substrate, four series have been designed in order to interact with large empty pockets of the active site: pyrimidoquinoline-2,4-diones (series A), pyrimidinedione linked to a pyrroloquinoline-1,3-diones (series B and C), the polycyclic heterocycle has been replaced by a pyrimidopyridopyrrolidinetetraone (series D). In each series, the tricyclic nitrogen heterocyclic moiety has been synthesised by a one-pot multicomponent reaction. Compared to 7-DX used as control, 2d, 2l, 2p (series A), 28a (series D), and the open intermediate 30 showed modest to good activities. A kinetic study confirmed that the most active compounds 2d, 2p are competitive inhibitors. Molecular docking analysis confirmed the interaction of these new compounds at the active binding site of TP and highlighted a plausible specific interaction in a pocket that had not yet been explored.